Clinical Presentation and Management of Histoplasmosis in Older Adults - Ledtke, Christopher; Tomford, J. Walton; Jain, Anil; Isada, Carlos M.; van Duin, David (Journal of the American Geriatrics Society (JAGS), 2012)
Objectives To describe the influence of age on clinical features of histoplasmosis. Design Retrospective single‐center cohort study. Setting Large tertiary care center. Participants All individuals who met criteria for probable or proven histoplasmosis between 1998 and 2008. Measurements Participants were divided into the following categories of histoplasmosis: acute pulmonary, chronic pulmonary, asymptomatic, disseminated, and other. Correcting for immune status, the influence of age at diagnosis on presentation, diagnosis, imaging, treatment, and all‐cause mortality was evaluated. Results In 347 participants with histoplasmosis, a number of characteristics were associated with age when evaluating participants according to diagnostic category. An age‐associated increase in asymptomatic histoplasmosis was observed (P < .001). In symptomatic pulmonary histoplasmosis, older adults were less likely to present with chest pain (P < .001) and less likely to have hilar lymphadenopathy on imaging (P = .04). Lower rates of seropositivity with older age were seen in asymptomatic (P = .04) but not other forms of histoplasmosis. Cavitary disease was associated with older age in chronic pulmonary histoplasmosis (P = .05). Treatment did not change with age. All‐cause mortality at 6 months was 4% and was associated with older age (P = .02). Conclusion Although most studied characteristics of histoplasmosis were similar, notable age‐related differences were present. Chronic cavitary disease and asymptomatic histoplasmosis were more common with older age. In acute histoplasmosis, the lack of chest pain and hilar lymphadenopathy may hinder diagnosis in older adults.